Acute and Subchronic Oral and Dermal Toxicological Studies of Salvia Verbenaca Extracts in Mice and Rats. Issue 1 (2nd January 2019) - Guaouguaou, Fatima-Ezzahrae; Taghzouti, Khalid; Oukabli, Mohamed; Masrar, Azlarab; Chabraoui, Layachi; Bouabdellah, Mounia; Es-Safi, Nour Eddine
ABSTRACT: The acute and subchronic toxicological effects of Salvia verbenaca extracts in hexane, ethyl acetate, n -butanol, were investigated. The extracts were not toxic at 2000 mg Kg −1 . A normal body weight evolution was observed during the 14 treatment days where there was no difference between the control and the treated groups. No abnormalities were seen in the haematological and biochemical parameters with the exception of an increase of the platelets. S. verbenaca may be recommended to boost platelets formation when compromised. Biochemical analysis revealed normal physiological levels of alanine transaminase (ALAT) and aspartate transaminase (ASAT). Histopathological examination showed a normal architecture with no morphological changes in the major vital examined organs.